2000
DOI: 10.1515/bc.2000.135
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tissue Kallikrein and Kinin Receptors in Angiogenic Microvascular Endothelial Cells

Abstract: Angiogenesis is the sprouting of new capillary blood vessels from pre-existing ones. The kinin family of vasoactive peptides, formed by the serine protease tissue kallikrein from its endogenous multifunctional protein substrate kininogen, is believed to regulate the angiogenic process. The aim of this study was to determine the expression of tissue kallikrein and kinin receptors in an in vitro model of angiogenesis. Microvascular endothelial cells from the bovine mature and regressing corpus luteum were used o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…HIST2H2BE encodes H2B histone, which serves as a cell proliferation marker and has been found overexpressed in serum and gastric cancer tissues by our group and others (Kamei et al, 1992;Hao et al, 2008). BDKRB2 was reported as an enhancer of angiogenesis in cancer (Plendl et al, 2000;Ishihara et al, 2001Ishihara et al, , 2002Ikeda et al, 2004). FGF7 encoded a member of the fibroblast growth factor (FGF) family.…”
Section: Discussionmentioning
confidence: 99%
“…HIST2H2BE encodes H2B histone, which serves as a cell proliferation marker and has been found overexpressed in serum and gastric cancer tissues by our group and others (Kamei et al, 1992;Hao et al, 2008). BDKRB2 was reported as an enhancer of angiogenesis in cancer (Plendl et al, 2000;Ishihara et al, 2001Ishihara et al, , 2002Ikeda et al, 2004). FGF7 encoded a member of the fibroblast growth factor (FGF) family.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that KLK12 is up-regulated in prostate cancer patients allows us to hypothesize the in vivo angiogenic role of KLK12 in prostate malignancy. Additionally, endothelial cells express KLK1 (Plendl et al , 2000 ), which is believed to support angiogenesis through the production of kinins (Emanueli et al , 2001 ). KLK1-mediated activation of kinin-downstream cascades has been revealed in prostate cancer-related angiogenesis (Giusti et al , 2005 ).…”
Section: Kallikrein-related Peptidases and Tumor Progressionmentioning
confidence: 99%
“…In PC-12 phaeochromocytoma cells, a Ca 2+ -dependent epidermal growth factor receptor (EGFR) transactivation has been reported to be involved in BKmediated ERK1/2 activation (Hall 1992); conversely, in A431 epidermoid cells, BK transinactivates EGFR and, independently of EGFR, BK activates ERK1/2 through both phosphoinositide 3-kinase (PI3K) and PKC (Graness et al 2000). BK is released by a kallikrein-kinin system, which is also present locally in breast tissue (Hermann et al 1995), where the released kinin could participate in tumourigenesis (Clements & Mukhtar 1977) and angiogenesis (Plendl et al 2000) by increasing vascular blood flow and creating new capillary vessels. We have previously shown that in normal breast cells in primary culture the activation of PKC-through the B 2 receptor acts in concert with ERK1/2 and PI3K pathways to induce cell proliferation (Greco et al 2004).…”
Section: Introductionmentioning
confidence: 99%